Development and validation of a high‐fidelity phonomicrosurgical trainer. (13th September 2016) - Klein, Adam M.; Gross, Jennifer
Abstract : Objectives: To validate the use of a high‐fidelity phonomicrosurgical trainer. Study Design: A high‐fidelity phonomicrosurgical trainer, based on a previously validated model by Contag et al., 1 was designed with multilayered vocal folds that more closely mimic the consistency of true vocal folds, containing intracordal lesions to practice phonomicrosurgical removal. A training module was developed to simulate the true phonomicrosurgical experience. A validation study with novice and expert surgeons was conducted. Methods: Novices and experts were instructed to remove the lesion from the synthetic vocal folds, and novices were given four training trials. Performances were measured by the amount of time spent and tissue injury (microflap, superficial, deep) to the vocal fold. An independent Student t test and Fisher exact tests were used to compare subjects. A matched‐paired t test and Wilcoxon signed rank tests were used to compare novice performance on the first and fourth trials and assess for improvement. Results: Experts completed the excision with less total errors than novices ( P = .004) and made less injury to the microflap ( P = .05) and superficial tissue ( P = .003). Novices improved their performance with training, making less total errors ( P = .002) and superficial tissue injuries ( P = .02) and spending less time for removal ( P = .002) after several practice trials. Conclusion: This high‐fidelity phonomicrosurgical trainer has been validated for novice surgeons. It can distinguish between experts and novices; and after training, it helped to improve novice performance. Level of Evidence: N/A. Laryngoscope, 127:888–893, 2017